THE INFLUENCE OF PERCEIVED EASE OF USE AND PERCEIVED USEFULNESS ON INTEREST IN USING PAYLATER - Ni Made Maharani Cahya Gita; I Made Pande Dwiana Putra (Adisam Publisher, 2025)
Paylater service is one of the financial technology innovations that can change the way people make financial transactions. Behind the development of technology, of course, there are dangers that accompany cybercrime, such as the rampant cases of pay later user data leakage. However, pay later users continue to increase. The purpose of this study was to determine the effect of perceived ease of use on interest in using paylater and to determine the effect of perceived usefulness on interest in using paylater. The research was conducted at the Undergraduate Accounting Study Program, Faculty of Economics and Business, Udayana University with a population of active undergraduate accounting students class of 2020. Determination of the sample in this study using purposive sampling technique so that 157 samples were obtained. Data collection was carried out using a questionnaire distribution method in the form of a Google form distributed via social media such as Whatssap. The data collected will be analyzed using multiple linear regression analysis techniques. The results found that perceived ease of use has a positive and significant effect on interest in using paylater and perceived ease of use has a positive and significant effect on interest in using paylater and perceived usefulness has a positive and significant effect on interest in using paylater. The implications of this research are the application of the technology acceptance model theory, as well as providing input to companies providing pay later services, and also encouraging the government to provide an education for financial technology services.